Multifaceted evolution focused on maximal exploitation of domain knowledge for the consensus inference of Gene Regulatory Networks - Segura Ortiz, Adrián; Giménez-Orenga, Karen; García-Nieto, José Manuel; Oltra, Elisa; Aldana-Montes, José Francisco (ELSEVIER, 2025)
The inference of gene regulatory networks (GRNs) is a fundamental challenge in systems biology, aiming to decipher gene interactions from expression data. However, traditional inference techniques exhibit disparities in their results and a clear preference for specific datasets. To address this issue, we present BIO-INSIGHT (Biologically Informed Optimizer - INtegrating Software to Infer GRNs by Holistic Thinking), a parallel asynchronous many-objective evolutionary algorithm that optimizes the consensus among multiple inference methods guided by biologically relevant objectives. BIO-INSIGHT has been evaluated on an academic benchmark of 106 GRNs, comparing its performance against MO-GENECI and other consensus strategies. The results show a statistically significant improvement in AUROC and AUPR, demonstrating that biologically guided optimization outperforms primarily mathematical approaches. Additionally, BIO-INSIGHT was applied to gene expression data from patients with fibromyalgia, myalgic encephalomyelitis, and co-diagnosis of both diseases. The inferred networks revealed regulatory interactions specific to each condition, suggesting its clinical utility in biomarker identification and potential therapeutic targets. The robustness and ingenuity of BIO-INSIGHT consolidate its potential as an innovative tool for GRN inference, enabling the generation of more accurate and biologically feasible networks. The source code is hosted in a public GitHub repository under the MIT license: https://github.com/AdrianSeguraOrtiz/BIO-INSIGHT. Moreover, to facilitate its reproducibility and usage, the software associated with this implementation has been packaged into a Python library available on PyPI: https://pypi.org/project/GENECI/3.0.1/.
Keywords: Genética; Ingeniería genética; Bioinformática; Ingeniería biomédica; Genómica; Inteligencia artificial - Aplicaciones médicas; Gene regulatory network; Inference; Expression data; Many-objective evolutionary algorithm; Consensus